Building permission-based relationships: new methods for gaining opt-in - Hanley, Michael; Christensen, Gerry; Strahan, Diane; Torbit, Chris; Darcey, James; Ramkumar, G.D. (Henry Stewart Talks, 2009)
Zoove StarStar (**) method of opt-in, Evolution of direct response, State of mobile marketing, Direct response business model, Benefits, Common short codes, What is the best way to mobilize your marketing campaigns?, How does mobile marketing work for brands?, Uses for common short codes, IVR, How can IVR be used in mobile marketing programs?, Voice is simple, Double opt-in and IVR, Image recognition based opt-in for mobile marketing, Advantages of image recognition opt-in, Image recognition technology
Archived at 2022/04/11